Test Analysis of Snake Spring Coupling Used in Belt Conveyor - Hong Meijuan; Lu Zhouyan (Jixie chuandong)
The static torsion test,no-load running and dynamic test of the snake spring coupling are designed. And the test results show that the maximum torque of the research and development snake spring coupling can reach to 160 000 N·m,the torque and the relative angle of the two halves coupling are non-linear relationship,the strength can meet the requirements of design,it is put into use on the test equipment.